SEMIOTIKA FERDINAND DE SAUSSURE DAN IMPLIKASINYA DALAM KAJIAN AL-QUR’AN - Mujahid, Said; Hasibuan, Rizky Ahmadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The study of the Qur'an and its interpretation has undergone significant development over time. Initially, traditional approaches were predominant, centered on the tafsīr bi al-ma’thūr method, which relies on the narrations of the Prophet, his companions, and the tābi‘īn. Over time, the emergence of tafsīr bi al-ra’y, which emphasizes reasoning and ijtihād, marked a shift towards more interpretative methods. This was followed by the development of various modern approaches such as thematic (mawḍū‘ī), literary, linguistic, historical, contextual, and hermeneutic interpretations. These developments reflect a dynamic response to the challenges of the times and the need for a Qur'anic reading that is more relevant to contemporary social, cultural, and intellectual contexts.Ferdinand de Saussure’s semiotic theory offers a linguistic approach that is particularly relevant for understanding texts, including religious texts like the Qur'an. Saussure divides linguistic signs into two main elements: the signifier and the signified, which, in the context of the Qur'an, can be employed to uncover implicit meanings behind the Arabic expressions and linguistic structures used. This study aims to analyze how the relationship between signifier and signified in Qur'anic verses can reveal deeper and more contextual meanings. Using a descriptive qualitative method and Saussure’s structural semiotic approach, this research identifies several verses with multiple, symbolic, or metaphorical meanings. The findings indicate that meaning in the Qur'an is not static but is constructed through a complex system of signs and contextual relations. This approach opens up broader interpretive possibilities while remaining within the boundaries of linguistic and exegetical scholarship. Thus, Saussurean semiotics can serve as a scientific approach for a more in-depth study of the Qur'an, particularly in understanding its linguistic and symbolic dimensions.